Peningkatan Kompetensi Guru SMPN 5 Kecamatan Harau dalam Merancang Rencana Pelaksanaan Pembelajaran (RPP) Melalui Pendampingan Berkala - Rosmaliwarnis, Rosmaliwarnis (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2017)
This research is School Action Research. It was done in SMPN 5 Kec. Harau which are entitled “Peningkatan Kompetensi Guru SMPN 5 Kecamatan Harau dalam Merancang Rencana Pelaksanaan Pembelajaran (RPP) Melalui Pendampingan Berkala”. There were 7 teachers who involved in this research. They got regularly mentoring from principal in order to lead them to design their Lesson Plan. There were 2 cycles in this research. The researcher used Lesson Plan Analysis form and field note to get the data. Before doing the research, the researcher analyzed the teacher’s lesson plan in order to get former data about the teacher’s competencies in designing lesson plan. It was found that the teachers’ competency was 70.56. it belongs to enough category. Then, after doing regularly mentoring from principal in cycle 1 the teacher’ competencies turned to 78.33. It means Good category. Finally, in cycle 2 the teachers’ competency became 87.78. So, based on the finding of the research, it can be concluded that regularly mentoring done by the principal can improve the teachers’ competencies in designing lesson plan.